A Customized Method for Recovery of Gaussian Beam Profile Emerging from Optical Fibers - Chughtai, Muhammad Tajammal (Engineering, Technology & Applied Science Research, 2024)
Loss of the Gaussian beam profile is frequently observed when lasers are combined with either classical or modern optics. This alteration in the beam profile affects the coherence length of the beam and produces an unfavorable output in laser applications. Poor cleaving of the optical fiber end face is the main cause of this problem, especially when cleaving is performed using low-precision equipment or nonstandard methods. This profile deformation prevents the intended output, which leads to an unanticipated leap in the laser beam profile from one Transverse Electromagnetic Mode (TEM) to another. In this work a method is proposed to mitigate this effect by attaching an optically flat glass piece to the end face of the fiber and using index matching gel. By guaranteeing a uniform distribution of the index matching gel, this technique enhances the consistency of the laser beam and successfully restores the Gaussian beam profile. Laboratory test results show that this technology is a viable substitute for conventional fiber-cleaving techniques and is rapid, easy, inexpensive, and dependable. While successful in controlled situations, other improvements, such as optical adhesives, are needed to achieve stable performance in settings that are prone to vibration.